Recent developments in acacia planting: proceedings of an international workshop held in Hanoi, Vietnam, 27-30 October 1997 - Turnbull, J.W.; Crompton, H.R.; Pinyopusarerk, K. (Australian Centre for International Agricultural Research, 1998)
The 1300 species of the genus Acacia extend around the globe, from Australia through Asia to Africa and the Americas. These nitrogen-fixing trees and shrubs grow in a range of environments and fill an important niche in natural ecosystems. They have also been planted as exotics in over 70 countries for land rehabilitation, shade and shelter, and to produce a range of wood and non-wood products including firewood, charcoal, building poles, tannins and fodder. In recent years extensive plantations have been established in Asia to provide wood pulp for paper and textile manufacture. This book contains 52 papers and 7 short communications on recent developments in planting tropical and subtropical acacias presented at a workshop held in Hanoi, Vietnam, 27-30 October 1997. It brings together the research results and experiences of scientists involved in developing new technologies for acacia planting in Asia and Australia and forest managers facing practical problems growing acacias in the region. Many papers refer to well-known species, such as Acacia auriculiformis, A. mangium and A. mearnsii, but others report the results of testing lesser-known species in a range of environments. The 57 participants at the workshop reviewed the major issues arising from the meeting, identified gaps in knowledge and made recommendations for future research. The key areas were: genetic resources and tree improvement, silviculture and site management, pests and diseases, physiology (including soil symbionts), social, economic and utilisation issues, and mechanisms to foster future collaboration.